2016
DOI: 10.1016/j.jneb.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Parental Nutrition Knowledge Rather Than Nutrition Label Use Is Associated With Adiposity in Children

Abstract: Objective-Determine how parental nutrition label use, label literacy, and nutrition knowledge may be associated with cardiovascular health in parents and their children.Design and Setting-Cross-sectional analyses of 2006 data from the Healthy Heart Project in Montreal, Canada.Participants-Among community recruited families, parents were predominantly mothers (n = 127 [80%]; mean age, 45.0 years) and half of their children were female (44%; mean age, 12.5 years).Main Outcome Measures-Blood pressure, lipids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…While research attention in this area has largely focused on nutrition label literacy 18,22,50 , our data demonstrate that identifying food sources of the macronutrients (Energy Sources in Food) and the ability to navigate food and nutrition products and marketing to choose between similar options (Consumer Skills) are two skills that have greater importance for choosing a healthy diet than an ability to read a food label. Although diet quality was not reported, a related study of parent nutrition knowledge and label use found that nutrition label literacy and nutrition knowledge was related to parental blood lipids, but only nutrition knowledge was related to child adiposity 51 .…”
Section: Discussionmentioning
confidence: 99%
“…While research attention in this area has largely focused on nutrition label literacy 18,22,50 , our data demonstrate that identifying food sources of the macronutrients (Energy Sources in Food) and the ability to navigate food and nutrition products and marketing to choose between similar options (Consumer Skills) are two skills that have greater importance for choosing a healthy diet than an ability to read a food label. Although diet quality was not reported, a related study of parent nutrition knowledge and label use found that nutrition label literacy and nutrition knowledge was related to parental blood lipids, but only nutrition knowledge was related to child adiposity 51 .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Tan et al [25] found that the awareness rate of nutrition knowledge was higher in the parent group compared to non-parent group as parents care more about their nutrition knowledge in order to improve their children’s nutritional status. Moreover, Kakinami et al [26] found that greater parental nutrition knowledge was associated with lower body mass index and other health related outcomes among children. Another study reported that high parental education was linked with less frequent snacking and more frequent weekly physical activity in children, compared to that of lower categories signifying the involvement of parents in nutrition intervention programs to improve dietary quality and nutritional behaviors of the entire family [27].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the SCT model, the literature shows parents' behaviours can directly affect their children's knowledge about health, self-efficacy, and outcome expectations. Parents who share their knowledge about diet and activity could influence their children's knowledge and outcome expectations (Kakinami, Houle-Johnson, & McGrath, 2016). Similarly, parental modelling of behaviour for their children results in children learning new skills and having increased motivations (e.g., outcome expectations) around health behaviours (Dwyer et al, 2017;Hughes, O'Connor, & Power, 2008;Joyal-Desmarais et al, 2019).…”
Section: Parents' Influence On Childrenmentioning
confidence: 99%